Historical analysis on the impacts of external institutions' support towards environmental management in a Philippine indigenous community - Rebancos, Carmelita M.; Ancog, Rico C.; Silvestre, Prima R.; Labapis, Dazzle R. (2010)
Historical analysis on the impacts of institutional support provided for by a religious group in collaboration with a foreign-funded non-governmental organization to the Sepuyo Alngan-Mangyan of Mindoro was conducted to evaluate...